Políticas Públicas Y Su Incidencia En El Cumplimiento De Las Obligaciones Tributarias De Los Comerciantes, Cantón Buena Fe Periodo 2023 - Bohórquez Anchundia, Katherine Stefania (2025)
The main objective of this study is to evaluate public policies in the Buena Fe Canton, which faced a persistent challenge related to compliance with tax obligations by its merchants. This problem was aggravated by the lack of clarity in public policies and knowledge of their tax obligations, generating confusion and significant difficulties for the local business community. The research is structured in three main parts. Firstly, an analysis of the current situation of public policies that affect the Buena Fe Canton is carried out, identifying strengths, weaknesses, opportunities and threats. Secondly, the factors that affect the non-compliance with tax obligations by merchants are investigated, considering aspects such as the complexity of the tax system and the lack of tax education. Finally, a communication plan is developed to guide merchants in the Buena Fe Canton towards adequate compliance with their tax obligations, promoting transparency and equity in the tax system. The findings of this research will provide valuable information to policy makers, government agencies and local institutions, as well as to traders themselves. They are expected to contribute to improving tax administration, increasing voluntary compliance with tax obligations and reducing tax evasion, thus promoting the sustainable economic development of the Buena Fe Canton.